A cultura de Guiné-Bissau revelada em experiência de ensino de português brasileiro para universitários - Filomena Caron, Monica (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
The objective of this paper is to examine several texts written in Brazilian Portuguese by undergraduated africans students belonging to exchange programs between Brazil e Guinea-Bissau. Our aim is to evaluate the uniqueness of their bilingualism and their literacy conditions. Based on their point of view, the work seeks to address their linguistic-textual productions, also exploring their possible contributions to the development of the integration processes of African students and foreigners in Brazilian public university. As a metodology analysis approach, we adopted the Indiciary Paradigm.The findings raised by the data highlighted the urgent need for a discussion of the variables involved in social mobility in Brazil and among the people and the process of creation and transmission of inequality through the cycle of life.